TATA KELOLA PEMERINTAHAN KOLABORATIF DALAM PENANGANAN KONFLIK DI KABUPATEN MESUJI - Danang Bintoro; Sampara Lukman; Kusworo Kusworo (EkoPreneur, 2020)
This research is entitled "Collaborative Governance in Conflict Management in Mesuji District, Lampung Province", what are the factors that support and hinder collaborative governance in handling conflicts in Mesuji Regency, Lampung Province, and what are the solutions in facing obstacles to collaborative governance in Conflict Handling in, Mesuji Regency Province Lampung This study used a qualitative research design with descriptive methods through an inductive approach. Research in obtaining informants uses non-probability sampling using snowball techniques, while the theory used in this study is Ansall and Gash's (2008) theory of Collaborative Governance. The results of this study indicate that there is a fairly good implementation of the Collaborative Governance concept by the Mesuji Regency Government in handling conflict, but there is an indication of a lack of coordination with the private sector, namely PT SIL Inhutani, which was granted permission to manage the register 45 area, especially in running a partnership program in management forest as a collaborative program in dealing with conflicts that have occurred for almost 10 years. Keywords: Collaborative Government, Conflict Management, Mesuji Conflict.